Monitoring Of Aquatic Insects As Bioindicators Of River Pollution - Gurning, Aksay K.; Wantasen, Sofia; Moniaga, Wilson M.; Watung, Jackson F.; Turang, Deflly A. S. (Sam Ratulangi University, 2026)
Aquatic insects serve as reliable indicators for water quality. This study aims to monitor and identify various types of aquatic insects as bioindicators of pollution found in the Kali Pineleng River, Pineleng District, Minahasa Regency. Sampling was carried out using kick sampling, hand picking, and sweeping techniques at three Sosongian River stations. The process of identifying aquatic insects used the identification key of McCafferty (1981); Morse et al (1994); Yule & Y. Hoi Sen (2004). After identification, the data obtained were analyzed descriptively and quantitatively using the biotic index formula and diversity index. The results of the study found eight orders of aquatic insects with a total of 263 individuals from 24 families. The Hemiptera order dominates the number of individuals, followed by Ephemeroptera and Trichoptera. Sampling was conducted at three stations showing variations in composition and number of specimens, with Station II having the largest number of individuals. The Shannon-Wiener diversity index (H’) showed a value of 1.45341, indicating moderate diversity in the aquatic insect community. In addition, the calculation of the Biotic Index (BI) at the three stations showed that the water quality was classified as